Electrochemical Sensor for the Anti-tuberculosis Drug Rifampicin on CuO@rGO-Nanocomposite-Modified GCE by Voltammetry Techniques - Sagar P.; Srivastava M.; Srivastava S.K. (My University, 2025)
Reduced-graphene-oxide layers (rGO) offer extremely subtle transducer thin-films and can be unified in interdigital micro-electrodes for various purposes. Understanding the functions and nature of rGO specially bio-compatibility, we can use this as potent-tool for the detection of antibiotic-drug Rifampicin (RFP) in standard/pharmaceutical samples. Herein, we synthesize CuO@rGO nano-composite and explored its potency for the preparation of electrochemically-active-electrodes. Catalytic-activity of as-synthesized CuO@rGO nano-composite is checked in 1.0 mM of Fe2+/3+ solutions and found to be more than three times higher current as compared to bare, rGO or CuO modified GCE. Subsequently, modified electrodes are used to detect RFP via two-techniques (differential-pulse voltammetry viz. DPV and cyclic-voltammetry viz. CV) in three-ways simultaneously. The CuO@rGO-modified-GCE (CuO@rGO/GCE) exhibits remarkable sensitivity with very low-detection-limit of 5–11 nM and long term-usage, which is far-better than other reported works. Non-interfering ability in existence of several body-interferents exposes that CuO@rGO/GCE could be an effective/ beneficial contrivance for the detection of RFP. © 2022 Wiley-VCH GmbH.